PENGKAJIAN PARAMETER FUNGSI VOLUME POHON MELALUI FOTO UDARA DI KALIMANTAN TIMUR - Ishak Sumantri; Haryono Haryono; Machfudh Machfudh (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The relationship between tree crown diameter and/or tree height which measured from aerial photos in tropical rain forest is the object of this study. Result of model analysis by crown diameter and tree height variable are as follows :In the harvested primary forest condition, the most appropriate model for all tree samples is : Y = 30,615 -1,580 D + 1,247 T + 0,037 D2 -0,021 DT with coefficient correlation r = 0,9637.The most appropriate model by crown diameter variable in the harvested primary forest condition for all trees samples is : Y = 1,732 + 0,214 D with r = 0,2971. For Meranti species, the most appropriate model is : Y = 6,684 - 0,555 D + 0,020 D2 with r = 0,664 and for Ulin species is: Y = - 37,736 + 2,738 D - 0,036 D2 with r = 0, 776. 3. The model and its analysis are valid for East Kalimantan only.